Building resilience through community-based post-disaster shelter reconstrution a case study in participatory technical assistance in Eastern Samar. - Varona, Maria Faith Yson (2016)
Post-disaster reconstruction efforts in shelter assistance guided by the principle of "build back better and safer" came in various froms and approaches after Typhoon Yolanda in 2013. Participatory technical assistance by non-goverment organizations (NGOs) in the island barangays of the municipality of Guiuan in Eastern Samar enabled typhoon survivors to take control and manage the reconstruction of their permanent shelters. The case study looked into challenges and learnings of participatory technical assistance in post-disaster reconstruction and the role of stakeholders. Results showed that challenges can be addressed with better multi-stakehoder coordination and project management and that site conditions and accessibility are always significant factors in project implementation.